Fast volumetric imaging of bound and pore water in cortical bone using three‐dimensional ultrashort‐TE (UTE) and inversion recovery UTE sequences. (5th August 2016) - Chen, Jun; Carl, Michael; Ma, Yajun; Shao, Hongda; Lu, Xing; Chen, Bimin; Chang, Eric Y.; Wu, Zhihong; Du, Jiang
Abstract : We report the three‐dimensional ultrashort‐TE (3D UTE) and adiabatic inversion recovery UTE (IR‐UTE) sequences employing a radial trajectory with conical view ordering for bi‐component T 2 * analysis of bound water ( T 2 * BW ) and pore water ( T 2 * PW ) in cortical bone. An interleaved dual‐echo 3D UTE acquisition scheme was developed for fast bi‐component analysis of bound and pore water in cortical bone. A 3D IR‐UTE acquisition scheme employing multiple spokes per IR was developed for bound water imaging. Two‐dimensional UTE (2D UTE) and IR‐UTE sequences were employed for comparison. The sequences were applied to bovine bone samples ( n  = 6) and volunteers ( n  = 6) using a 3‐T scanner. Bi‐component fitting of 3D UTE images of bovine samples showed a mean T 2 * BW of 0.26 ± 0.04 ms and T 2 * PW of 4.16 ± 0.35 ms, with fractions of 21.5 ± 3.6% and 78.5 ± 3.6%, respectively. The 3D IR‐UTE signal showed a single‐component decay with a mean T 2 * BW of 0.29 ± 0.05 ms, suggesting selective imaging of bound water. Similar results were achieved with the 2D UTE and IR‐UTE sequences. Bi‐component fitting of 3D UTE images of the tibial midshafts of healthy volunteers showed a mean T 2 * BW of 0.32 ± 0.08 ms and T 2 * PW of 5.78 ± 1.24 ms, with fractions of 34.2 ± 7.4% and 65.8 ± 7.4%, respectively. Single‐component fitting of 3D IR‐UTE images showed a mean T 2 * BW of 0.35 ± 0.09 ms. The 3D UTE and 3D IR‐UTE techniques allow fast volumetric mapping of bound and pore water in cortical bone. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Maps of bound water T2* (A), pore water T2* (B), bound water fraction (C) and pore water fraction (D) derived from bi‐component fitting of five sets of dual‐echo 3D‐UTE‐Cones images of a bovine cortical bone sample.